ANALISIS MANAJEMEN KEPALA SATUAN PENDIDIKAN NONFORMAL SANGGAR KEGIATAN BELAJAR DALAM MENINGKATKAN PRODUKTIVITAS KINERJA PAMONG BELAJAR - Rosyati, Tati Trisnawati (Wali Pikir: Journal Of Education, 2023)
The problem in this research is that the quality of tutors does not meet standards. The performance indicators used are work quality, attendance, punctuality, initiative, ability and communication. This research aims to describe and analyze the role of the Head of SPNF SKB as a manager in increasing the productivity of learning tutors’ performance at UPT SPNF. The research method used is descriptive qualitative analysis. Data collection techniques using observation studies, interviews and documentation. Data analysis techniques, namely narrative analysis techniques, text meaning analysis, conversation analysis and scientific theory analysis. Data were tested by triangulating data sources from various appropriate research tests. The research results show that the management role of the Head of SNPF SKB is in increasing the productivity of the teaching performance of SKB Cimahi City and SKB Bandung City, namely in Early Childhood Education and Package C.